Preclinical Evaluation of Intraoperative Low-Energy Photon Radiotherapy Using Spherical Applicators in Locally Advanced Prostate Cancer - Buge, François; Chiavassa, Sophie; Hervé, Chloé; Rigaud, Jérôme; Delpon, Grégory; Supiot, Stéphane (Frontiers in Oncology, 2015)
Background: Surgery plus adjuvant radiotherapy is standard care for locally advanced prostate cancer (stage pT3R1). Intraoperative low-energy photon radiotherapy offers several advantages over external beam radiotherapy, and several systems are now available for its delivery, using spherical applicators which require only limited shielding. The aim of this study was to evaluate the feasibility of this technique for the prostate bed. Materials & Methods: Applicators were assessed using MRI image data and cadaveric dissection. In cadavers, targeted tissues, defined as a urethral section, both neurovascular bundle sections, the bladder neck and the beds of the seminal vesicles, were marked with metallic surgical clips. Distances between clips and applicator were measured using CT. A dosimetric study of the application of 12 Gy at 5mm depth was performed using CT images of prostatectomized cadavers. Results: Using MRI images from 34 prostate cancer patients, we showed that the ideal applicator diameter ranges from 45 to 70 mm. Using applicators of different sizes to encompass the prostate bed in nine cadavers, we showed that the distance between target tissues and applicator was less than 2 mm for all target tissues except the upper extremity of the seminal vesicles (19 mm). Dosimetric study showed a good dose distribution in all target tissues in contact with the applicator, with a low probability of rectum and bladder complication. Conclusions: Intraoperative radiotherapy of the prostate bed is feasible, with good coverage of targeted tissues. Clinical study of safety and efficacy is now required.